The Role Of Gen Z In Increasing Participation Rates In The 2024 Regional Elections - M. Faisal Husna; Febrian Abdan Sakuroh; Mahrofa Zagia Natasya; Nur Annisa Putri; Leony Fansiska Agustina; Putri Sadilla; Mutiara, Mutiara; Isnaini Fadila Putri; Dimetrio Ginting; Andrian Maulana (Sean Institute, 2025)
The 2024 Regional Head Election is a strategic moment in strengthening democracy in Indonesia. One of the main challenges is increasing voter participation rates, especially among young people. Generation Z, as a group that grew up in the digital era, has great potential to influence increased regional election participation. This article aims to analyze the role of Generation Z in increasing participation rates for the 2024 regional elections. In this context, Generation Z has a strategic role because of their significant numbers and unique characteristics as a digitally connected and change-oriented generation. The results of this research show that Generation Z has great potential to become agents of change through various strategies through the use of social media for political campaigns, dissemination of accurate information and education about the importance of elections. This article concludes that with the right empowerment, Generation Z can be the main driver in creating regional elections that are more inclusive, transparent and have high participation.